PENILAIAN LAHAN PERSAWAHAN DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA DI KECAMATAN CIAMPEL KABUPATEN KARAWANG - , Sinta Yulyanti, Dra. Wahyu Hidayati, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to apply the property valuation models using the income approach to determine the market value and the factors that influance of rice filelds in Kabuapten Karawang Kecamatan Ciampel. The data used consisted of land, cost of production, annual income, distance from home (residential), the distance from the highway with a sample of 34 data. The method of analysis used in this study is to calculate the value of paddy field using direct capitalization income approach, to determine the factors that affect the value of land use OLS regression analysis. The results showed that the assessment of paddy fields in the Kecamatan Ciampel, Kabuapten Karawang uses direct capitalization method produces an average value of Rp944.666.667 and market data yield an average value of Rp855.034.00.Rekonsiliasi of the two approaches is obtained assetsRp913.310.861.While based on the results of the regression equation paddy fields are widely variable, distance, NOI. From the estimation results obtained extensive variable coefficients positive and significant at the 10 percent level. The distance to the main road and no significant negative effect on the level of 10 percent. NOI negative and not significant at the level of 10 percent. The indeoendent variables (area, distance, NOI) simultaneously significant effect on the level of 10 percent of the land value in the show if the value of F-statistic for 6,071286.